Penerapan Lean Manufacturing untuk Mengurangi Waste pada Produksi Absorbent - Agung Ravizar; Rosihin Rosihin (Universitas Serang Raya, 2018)
This study aims to reduce the waste that occurs on each workstation and has an impact on increasing productivity and reducing production costs caused by waste that occurs during production. The data used for this study is quantitative data obtained by direct observation to the relevant departments regarding the problem of identifying waste that occurs — data taken from observations as much as 30 times the collection of data and historical data used from January 2016 to June 2017. By using the value stream mapping method on lean manufacturing, it can be seen that there are five types of waste from the existing seven waste. The five wastes are unnecessary motion, waiting, reject, transportation and in-process processes. From the results of the value stream mapping carried out a reduction in waste on each workstation with a total reduction of waste that occurs at 66.97 tons / year or 18.6% on waste gel and 88.8 tons / year or 19.3% at waste powder and there was a reduction in the changeover process for 45 minutes or 12.16% of the total changeover time before the improvement. Also, there was also an increase in the production process speed of 2 minutes 47 seconds or 4.52% from the lead time of the previous production process, 61 minutes 34 seconds to 58 minutes 47 seconds.